2012
DOI: 10.3390/a5030330
|View full text |Cite
|
Sign up to set email alerts
|

Use of Logistic Regression for Forecasting Short-Term Volcanic Activity

Abstract: An algorithm that forecasts volcanic activity using an event tree decision making framework and logistic regression has been developed, characterized, and validated. The suite of empirical models that drive the system were derived from a sparse and geographically diverse dataset comprised of source modeling results, volcano monitoring data, and historic information from analog volcanoes. Bootstrapping techniques were applied to the training dataset to allow for the estimation of robust logistic model coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…In 2012, William N. Junek used decision tree frameworks and logistic regression to forecast volcanic activity. Cross validation showed that the algorithm provided desirable predictive ability [7] . In addition to geological aspects, logistic regression is widely used in other industries [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, William N. Junek used decision tree frameworks and logistic regression to forecast volcanic activity. Cross validation showed that the algorithm provided desirable predictive ability [7] . In addition to geological aspects, logistic regression is widely used in other industries [8,9] .…”
Section: Introductionmentioning
confidence: 99%